2021
DOI: 10.1111/cts.12962
|View full text |Cite
|
Sign up to set email alerts
|

Altered vitamin A metabolism in human liver slices corresponds to fibrogenesis

Abstract: All‐trans‐retinoic acid (atRA), the active metabolite of vitamin A, has antifibrogenic properties in vitro and in animal models. Liver vitamin A homeostasis is maintained by cell‐specific enzymatic activities including storage in hepatic stellate cells (HSCs), secretion into circulation from hepatocytes, and formation and clearance of atRA. During chronic liver injury, HSC activation is associated with a decrease in liver retinyl esters and retinol concentrations. atRA is synthesized through two enzymatic step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…For reasons that remain unclear, data show that hepatic retinoid levels are reduced in high-fat diet (HFD) and genetic murine models of NAFLD [ 71 , 72 , 73 , 74 ], human NAFLD [ 71 , 72 , 75 , 76 ], and acute liver injury [ 77 ]. The liver is the primary organ for retinoid storage, with approximately 80% of the total body retinoid pool stored as retinyl esters in triglyceride-rich lipid droplets in quiescent hepatic stellate cells (HSCs), specialized mesenchymal cells of the liver [ 78 ].…”
Section: Non-alcohol-associated Fatty Liver Diseasementioning
confidence: 99%
“…For reasons that remain unclear, data show that hepatic retinoid levels are reduced in high-fat diet (HFD) and genetic murine models of NAFLD [ 71 , 72 , 73 , 74 ], human NAFLD [ 71 , 72 , 75 , 76 ], and acute liver injury [ 77 ]. The liver is the primary organ for retinoid storage, with approximately 80% of the total body retinoid pool stored as retinyl esters in triglyceride-rich lipid droplets in quiescent hepatic stellate cells (HSCs), specialized mesenchymal cells of the liver [ 78 ].…”
Section: Non-alcohol-associated Fatty Liver Diseasementioning
confidence: 99%
“…Indeed, the primary role of ALDH1A1 is the detoxification of reactive lipid aldehydes in the human lens and mouse liver 30,31 . Our group previously reported that whereas ALDH1A1 expression is high in human hepatocytes, retinoid homeostasis localizes to the stellate cells, 18 again indicating an alternative function for ALDH1A1 in tissues with high exposure to reactive lipids. These data are consistent with a prior mouse study demonstrating that high fat feeding led to increased ALDH1A1 expression but not tissue at RA concentrations in white adipose tissue 25 and provide a potential model to reconcile these seemingly discordant findings.…”
Section: Discussionmentioning
confidence: 91%
“…Fundamental questions regarding vitamin A metabolism within human adipose tissue remain unanswered, including which enzymes are responsible for at RA biosynthesis. The aldehyde dehydrogenase 1A (ALDH1A) family of enzymes, 16,17 also known as retinaldehyde dehydrogenases (RALDHs), are the predominant enzymes contributing to at RA biosynthesis in many tissues, but their expression varies among tissues, cell types, and with developmental stage 18–20 . In addition, aldehyde oxidase (AOX) may contribute to at RA biosynthesis 21 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 C, right). Interestingly, in activated HSCs, which are known to lose their vitamin A stores ( 25 , 26 ), Lrat and Kiaa1363 mRNA expression was inversely regulated. Since Lrat expression in liver is known to be vitamin A sensitive ( 27 ), we explored the possibility whether also Kiaa1363 mRNA would be differently expressed in liver of mice when fed different vitamin A feeding regimes.…”
Section: Resultsmentioning
confidence: 99%